Both morphological and molecular data are crucial for describing new species — a case study on the genus Oreocharis (Gesneriaceae) - Xie, Zhi; Peng, Nana; Xie, Genglin; Wen, Fang; Kong, Hanghui (Frontiers in Plant Science, 2025)
The concept and definition of species are fundamental in taxonomy and evolutionary biology. Traditionally, new species have been described primarily based on the morphological species concept (MSC). However, environmental factors may drive morphological convergence among distantly related species. In addition, widespread hybridization, gene flow, and incomplete lineage sorting (ILS) among closely related taxa can further obscure phylogenetic relationships and hinder accurate species delimitation. In the current study of the genus Oreocharis Benth. (Gesneriaceae: Didymocarpoideae), we built upon a broad phylogenomic framework established in previous work. We incorporated transcriptome data of six specimens from Sichuan, China, and conducted detailed morphological comparisons and phylogenomic analyses. The integrative results reveal that these specimens represent a previously unrecognized lineage, which we formally describe here as Oreocharis yanbianensis Z. Xie & H. H. Kong, sp. nov. Our study demonstrates the importance of combining morphological and genomic data to improve the accuracy and robustness of species discovery and classification, especially in morphologically variable plant groups.